2000
DOI: 10.1111/j.1469-445x.2000.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide Synthase Inhibition on Renal Circulation and Excretory Function in Anaesthetized Rats

Abstract: The effects of nitric oxide synthase (NOS) inhibition (effected using L-NAME, 14 mg (kg body mass (BM))(-1), administered intravenously) on systemic and renal circulation and renal excretory function has been investigated in anaesthetized Wistar rats subjected to one of two different degrees of isotonic extracellular (EC) volume expansion (40 and 60 ml x kg(-1) (240 min)(-1)). The administration of L-NAME resulted in an increase in mean arterial blood pressure and total peripheral vascular resistance (TPR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…There have been several reports demonstrating decreased renal blood flow, increased renal vascular resistance and elevated SBP after treatment with nonselective NOS inhibitors in rats. 40,41 Our results are according to these statements, since, in the presence of L-NAME, the administration of a NOS substrate, L-arginine, was able to return to baseline values of haemodynamic variables (see Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…There have been several reports demonstrating decreased renal blood flow, increased renal vascular resistance and elevated SBP after treatment with nonselective NOS inhibitors in rats. 40,41 Our results are according to these statements, since, in the presence of L-NAME, the administration of a NOS substrate, L-arginine, was able to return to baseline values of haemodynamic variables (see Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…There have been a number of reports demonstrating decreased renal blood flow, increased renal vascular resistance and elevated systemic blood pressure after treatment with nonselective NOS inhibitors in anesthetized and conscious rats [38,39,40,41]. Impairment of NO production via eNOS blockade is involved in these hemodynamic changes; however, the role of NO derived from nNOS in the control of the renal circulation has not been determined.…”
Section: Effects Of Neurogenic No On Renal Vascular Function and Bloomentioning
confidence: 99%
“…In this sense, several authors have shown that impaired urinary diluting capacity would be associated with an upregulation of arginine vasopressin (AVP)-mediated AQP2 expression and membrane trafficking in the inner medulla in the hypothyroid state [9][10][11][12]. On the other hand, studies conducted in both humans and experimental animals demonstrate that NO decreases renal vascular resistance and increases GFR, natriuresis and water excretion [13,14]. It is well known that AVP increases collecting duct water permeability by enhancing AQP2 channel insertion in the apical membrane of principal cells through the AVP/cAMP pathway [14].…”
Section: Introductionmentioning
confidence: 99%